Effectiveness of a Clinical Decision Support System for Pointing Device Prescription. - Danial-Saad, Alexandra; Kuflik, Tsvi; Weiss, Patrice L.; Schreuer, Naomi (American Journal of Occupational Therapy)
OBJECTIVE. We present a novel, knowledge-driven approach to prescription of pointing devices that uses the Ontology-Supported Computerized Assistive Technology Recommender (OSCAR), a clinical decision support system (CDSS). METHOD. Fifty-five occupational therapists were divided into four groups: two assistive technology (AT) expert groups and two novice groups. Novice Group 1 used the OSCAR CDSS for the prescription process, and Novice Group 2 used the conventional method. OSCAR’s effectiveness and its impact on users were evaluated. RESULTS. The ability of Novice Group 1 to make suitable pointing device prescriptions was similar to that of the two expert groups and was significantly better than that of Novice Group 2. The system positively affected Novice Group 1’s learning of the prescription process. CONCLUSION. The structure and organized framework for clinical reasoning of the OSCAR CDSS appear to enable occupational therapy practitioners inexperienced in AT to achieve performance levels comparable to those of expert